1A three-sample study of perfectionism and field test performance in athletes - Mallinson-Howard, S. H.; Madigan, D. J.; Jowett. G. E. (European Journal of Sport Science, 2021)
Field tests are commonly used by sport scientists for performance monitoring and evaluation. While perfectionism predicts performance in a range of contexts, it is currently unclear whether perfectionism predicts performance in such tests. To address this lack of understanding, the present study examined the relationships between perfectionism and fitness-based field test performance across three athlete samples. After completing a measure of perfectionism (striving for perfection and negative reactions to imperfection), sample one (n = 129 student athletes) participated in a series of countermovement jumps and 20-metre sprint trials, sample two (n = 136 student athletes) participated in an agility task, and sample three (n = 116 junior athletes) participated in the Yo-Yo intermittent recovery test (level one). Striving for perfection predicted better sprint and Yo-Yo test performance. Negative reactions to imperfection predicted worse sprint performance. Mini meta-analyses of the combined data (N = 381) showed that striving for perfection was positively related to performance (r+ = .24), but negative reactions to imperfection was unrelated to performance (r+ = -.05). The present findings indicate that striving for perfection may predict better fitness-based field test performance, while negative reactions to imperfection appears to be ambiguous.